Program development and initial experiences with the online class “Erste Hilfe Kasten – Allgemeinmedizin” - Seiler, Sabine; Schelter, Frederik; Nöfer, Eberhard; Roos, Marco (GMS Journal for Medical Education)
Objective: This project aims to provide doctors in postgraduate training (ÄiW) in general medicine with business knowledge of practice management through a modular training program within an e-learning environment, thereby reducing important barriers to establishing a medical practice. Methodology: To develop the concept, a needs analysis (interviews with medical specialists, ÄiW, and medical students) was combined with teaching and informational materials from the Association of Statutory Health Insurance Physicians. Results: The developed e-learning concept consists of twelve self-contained modules that include various formats (teaching letters, videos, audio slide presentations, and checklists) for knowledge transfer and reflection. By May 2024, 72 participants had started using the class. The needs initially stated by the participants largely corresponded with the content offered. So far, the possibility of feedback to adapt the content or questions about the content have not been used. Conclusion: The modular e-learning class presented here covers business management topics in general practice and can help reduce this important barrier.